2023
DOI: 10.21203/rs.3.rs-3210421/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phase 3 Trial of Recombinant Human Alkaline Phosphatase for Patients with Sepsis-Associated Acute Kidney Injury (REVIVAL)

Peter Pickkers,
Derek Angus,
Kristie Bass
et al.

Abstract: Purpose: Ilofotase alfa is a human recombinant alkaline phosphatase with reno-protective effects that showed improved survival and reduced MAKE90 in sepsis-associated acute kidney injury (SA-AKI) patients. ‘REVIVAL’, was aphase 3 trial, conducted to confirm its efficacy and safety. Methods: In this international double-blinded randomized-controlled trial, SA-AKI patients were enrolled <72 hours on vasopressor and <24 hours of AKI. The primary endpoint was 28-day all-cause mortality. The key secondary end… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In 1997, Dr. Poelstra et al found that alkaline phosphatase can dephosphorylate and inactivate endotoxin, suggesting that alkaline phosphatase can be used to treat acute kidney injury, resulted from endotoxin-related sepsis [11][12][13][14]. A multicenter clinical study by Dr. Peters showed that a Human Recombinant AP (recAP) was safe and effective in patients with sepsis-associated acute kidney injury [15] In conclusion, recAP is one of the limited pharmaceutical treatment options for sepsis-associated acute kidney injury undergoing clinical trial testing [16].…”
Section: Clinical Application Of Alkaline Phosphatasementioning
confidence: 99%
“…In 1997, Dr. Poelstra et al found that alkaline phosphatase can dephosphorylate and inactivate endotoxin, suggesting that alkaline phosphatase can be used to treat acute kidney injury, resulted from endotoxin-related sepsis [11][12][13][14]. A multicenter clinical study by Dr. Peters showed that a Human Recombinant AP (recAP) was safe and effective in patients with sepsis-associated acute kidney injury [15] In conclusion, recAP is one of the limited pharmaceutical treatment options for sepsis-associated acute kidney injury undergoing clinical trial testing [16].…”
Section: Clinical Application Of Alkaline Phosphatasementioning
confidence: 99%